Analisis Putusan Pengadilan Agama Dalam Perkara Pembagian Harta Bersama Akibat Perceraian Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan dan Kompilasi Hukum Islam : Studi Putusan-Putusan Di Pengadilan Agama Rantau Prapat - Edi Sutra Ritonga; Hasballah Thaib; Hasim Purba; Utari Maharany Barus (USU LAW JOURNAL, 2019)
Abstract. In the law of number 1, 1974 about the marriage in section one stated that marriage is the bond between a man and woman as a couple with a goal to form the happiness and everlasting family based on the believe in the one supreme God, therefore the marriage always hoped going on with the happiness, yet the certain condition the divorce is the case that cannot be avoided as a reality. Divorce is a law phenomenon that will bring the law results; one of them is a collective treasure. Section 37 of the verse 1 of the law number 1, 1974 about marriage states that if the marriage is break because of divorce, so the collective treasure will be set based on its laws, but didn’t determine how is the portion of husband and wife that divorced. The explanation of this section 37 states its laws are religion law, tradition law, and the other laws. In addition to the law number one, 1974 about marriage, in Indonesia also occurred the Islamic law compilation that related to division of collective treasure in the same manner as set in the section 96 and 97 Islamic Law Compilation. Based on those cases, so the problems that searched in this research is: how is the conducting of collective treasure division that caused of divorce in its practice in Rantau Prapat Religion Court and the obstacle in conducting of collective treasure division. The method approach that used in this research is juridical empiric approach and it is descriptive analytic. Based on the result of this research, can be concluded that the division of collective treasure based on the judge considerations dodge in determining verdict after examining and administering justice step by step based on procedure of civil law, so the judge in determining the verdict refers to the law of number one 1974 about marriage in section 35 to 37  and Islamic law Compilation in section 85 to 97,  jurisprudence, Supreme Court of Indonesia, Holy Qur’an in sura At-Tholaq: 7, An-Nahl: 90, An-Nisa:58 and 32, it is applied law and the synchrony in resolving legal action in this time, so the assets treasure that acquired either from the husband or the wife become collective right along is not determined in the marriage deal and if the marriage is break, each of them have a half from that treasure, because a long the marriage there are the collective treasure. The obstacles that often appear in conducting collective treasure division is they usually do not have the complete prove, is it true a collective right or not. Example: the large measure land and the limits are not clear, and the buyer place that was died.   Key words: divorce, collective treasure division, religion court verdict.